On the Association Between Musical Training, Intelligence and Executive Functions in Adulthood - Criscuolo, Antonio; Bonetti, Leonardo; Särkämö, Teppo; Kliuchko, Marina; Brattico, Elvira (Frontiers in Psychology, 2019)
Converging evidence has demonstrated that musical training is associated with improved perceptual and cognitive skills, including executive functions and general intelligence, particularly in childhood. In contrast, in adults the relationship between cognitive performance and musicianship is less clear and seems to be modulated by a number of background factors, such as personality and socio-economic status. Aiming to shed new light on this topic, we administered the Wechsler Adult Intelligence Scale III (WAIS-III), the Wechsler Memory Scale III (WMS-III) and the Stroop Test to 101 Finnish healthy adults grouped according to their musical expertise (non-musicians, amateurs and musicians). After being matched for socio-economic status, personality traits and other demographic variables, adult musicians exhibited higher cognitive performance than non-musicians in all the mentioned measures. Moreover, linear regression models showed significant positive relationships between executive functions (working memory and attention) and the duration of musical practice, even after controlling for intelligence and background variables, such as personality traits. Hence, our study offers further support for the superior cognitive abilities of musically trained individuals, even in adulthood.